ERP Effectiveness in Improving Production Efficiency - Alfikri, Valbian; Anwar, Adi Khairul; Prananta, Gery; Sulistiani, Heni (LPPM STIKI Malang, 2024)
This research specifically investigates how the implementation of ERP systems impacts the operational performance of manufacturing companies. By analyzing the literature and conducting case studies, this research uncovers potential efficiency improvements in various aspects, including reduced production time, optimized use of resources, and improved data quality. The results of this study are expected to provide valuable recommendations for manufacturing companies in implementing ERP effectively and achieving competitive advantage.